Implementasi Model Penyaluran Program Bantuan Sosial Pemberdayaan Ekonomi Untuk Petani Serai Wangi Di Kabupaten Gayo Lues Provinsi Aceh - Adam Adam (Universitas Medan Area, 2020)
The purpose of this study was to analyze the Implementation, inhibiting and supporting factors, the concept of distribution of social assistance programs for economic empowerment for citronella farmers in Gayo Lues Regency. Data collection techniques through interviews, observation, documentation, triangulation. The results showed that the implementation of the distribution model of social assistance programs for economic empowerment was carried out by a model by name by address and the implementation was carried out effectively marked by the achievement of the minimum target of land planted by lemongrass farmers according to the name and address of the farmer. The inhibiting factor, when viewed from the contents of the policy, is still lack of support from human resources, funding sources, infrastructure, and technology. Inhibiting factors, when viewed from the policy context include: Various interests of individual implementors involved in program implementation, law enforcement, farmer business locations, and marketing. Supporting factors for policy content are the influence of fewer interests, changes in responsible behavior, transparency, clear tasks and functions, high work motivation, good coordination and communication, decision making by regional leaders, and strong support from the farming community. Supporting the policy context is the existence of a legal umbrella, fewer interests, empowerment oriented, based on regulations. The concept of channeling the Social Assistance Program for Economic Empowerment of Serai Wangi Farmers by using the PASTI Concept (Supervision, Accountability, Resources, Legal Actions, Implementation).